2020
DOI: 10.1186/s12889-020-8373-x
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with loss-to-follow-up of HIV-positive mothers and their infants enrolled in HIV care clinic: A qualitative study

Abstract: Background: In Malawi, loss to follow-up (LTFU) of HIV-positive pregnant and postpartum women on Option B+ regimen greatly contributes to sub-optimal retention, estimated to be 74% at 12 months postpartum. This threatens Malawi's efforts to eliminate mother-to-child transmission of HIV. We investigated factors associated with LTFU among Mother-Infant Pairs. Methods: We conducted a qualitative study, nested within the "Promoting Retention Among Infants and Mothers Effectively (PRIME)" study, a 3-arm cluster ran… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 41 publications
(85 reference statements)
3
13
0
Order By: Relevance
“…Losses to follow-up among women who experienced antiretroviral drug side effects were higher than a woman who does't experience antiretroviral drug side effects. The result is in line with studies in Malawi [47], and Nigeria [48].…”
Section: Discussionsupporting
confidence: 92%
“…Losses to follow-up among women who experienced antiretroviral drug side effects were higher than a woman who does't experience antiretroviral drug side effects. The result is in line with studies in Malawi [47], and Nigeria [48].…”
Section: Discussionsupporting
confidence: 92%
“…However, mothers who commenced ART prior to enrolment had higher infant and maternal retention than those who commenced ART during pregnancy which may suggest these mothers may have had advanced appreciation and/or understanding of the benefits of ART/adherence to healthcare services due to previous experience. Conversely, married women had a 60% increased hazard of non-retention compared with single women, suggesting a non-supportive husband or family environment may contribute to reduced maternal retention, consistent with a previous MTCT study in Malawi, [ 31 ] and a qualitative study nested within the PRIME study of HIV-infected mothers and health care providers [ 32 ].…”
Section: Discussionsupporting
confidence: 80%
“…While receiving an infant’s HIV test result was associated with reduced infant retention, consistent with other studies, [ 12 14 ] no association was found with maternal retention. Conversely, the qualitative study nested in the PRIME study found receiving an infant’s HIV negative test result was reported as being a contributing factor for maternal non-retention to HIV care, despite receiving counselling of the importance of adherence to sustained HIV care [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Under the option B+, women diagnosed during pregnancy or breastfeeding are immediately initiated on ART irrespective of CD4 count or clinical staging, which makes them likely to miss out on key initiation procedures such as psychological preparation, an essential aspect in retention in care [ 12 , 13 ]. Women under option B+ are likely not to be well counselled and tend to suffer from stigma related challenges including lack of disclosure [ 8 , 10 ]. this concern has been reported to be a hindrance to the success of option B+ and the test and treat strategies where, clients initiated under these programs possess a higher possibility of dropping out of care as they perceive themselves as healthy compared with those initiated under the conventional WHO staging criteria [ 8 , 13 , 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%